2022
DOI: 10.22207/jpam.16.2.48
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant Methicillin-Resistant Staphylococcus aureus in Northeastern Saudi Hospitals

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for serious threats to human health, causing various syndromes worldwide. Here, our purpose was to estimate the prevalence of nosocomial MRSA among isolates from King Khalid Hospital (KKH) and Maternity and Children Hospital (MCH) at Hafar Al-Batin Governorate, Saudi Arabia, and to determine the resistance of these isolates to common antibiotics used for treatment. One-hundred clinical specimens were collected from admitted patients during a six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Locally, Alaklobi and colleagues found that the prevalence of MRSA was 23.3 % among outpatient children in Riyadh Saudi Arabia ( Alaklobi et al, 2015 ). While MRSA prevalence was 60 % in a maternity hospital in Hafar Al-Batin in eastern region in Saudi Arabia ( Aljeldah et al, 2022 ). Globally, the range of MRSA prevalence in maternal patients ranges from 2.1 % to 41 % ( Chen et al, 2006 , Reusch et al, 2008 , Nourollahpour Shiadeh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Locally, Alaklobi and colleagues found that the prevalence of MRSA was 23.3 % among outpatient children in Riyadh Saudi Arabia ( Alaklobi et al, 2015 ). While MRSA prevalence was 60 % in a maternity hospital in Hafar Al-Batin in eastern region in Saudi Arabia ( Aljeldah et al, 2022 ). Globally, the range of MRSA prevalence in maternal patients ranges from 2.1 % to 41 % ( Chen et al, 2006 , Reusch et al, 2008 , Nourollahpour Shiadeh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, tissue was dried at room temperature under shade, ground with the help of an electric grinder, and stored. Escherichia coli , Staphylococcus aureus , Alternaria alternata , and Fusarium oxyporium were brought from previous work at the University of Hafr Al Batin [ 30 ]. All the required chemicals, i.e., copper salt (CuSO 4 ·5H 2 O) was bought from Sigma–Aldrich through Science Traders.…”
Section: Methodsmentioning
confidence: 99%
“…Planning an updated treatment regimen requires frequent knowledge of the local antimicrobial sensitivity pattern [12]. The prevalence of UTIs is high, and bacterial resistance to antibiotics is spreading globally, especially in Saudi Arabia [13].…”
Section: Introductionmentioning
confidence: 99%